Simultaneous Occurrence of Ovarian Teratoma and Endometrial Cystic Hyperplasia with Pyometra in a Labrador Retriever Bitch - Garcia, Daniel Cardoso; da Silva, José Wagner Amador; de Gutierrez, Letícia Gutierrez; Garcia, Larissa Eckmann Mingrone; de Sá, Marcelo Jorge Cavalcanti (Acta Scientiae Veterinariae, 2021)
Background: Ovarian teratoma is a rare tumor that occurs in dogs. Its origin comes from embryonic cells of the notochord and it is a unipotent tumor. Pyometra is the accumulation of purulent content in the uterine lumen. Cystic endometrial hyperplasia is one of the factors predisposing a dog to the development of pyometra. The safest and most efficient treatment for pyometra is ovariohysterectomy. The purpose of this report was to describe a case of ovarian teratoma and cystic endometrial hyperplasia with concomitant pyometra in a Labrador Retriever Bitch. Case: A 10-year-old bitch Labrador Retriever, weighing 42 kg, was evaluated at Animal Care Barueri Veterinary Clinic, in Barueri, São Paulo. The patient was referred from another veterinary service to our clinic for an ovariohysterectomy and removal of an intestinal foreign body as previous ultrasonography (US) had indicated the presence of pyometra and a foreign body in the descending colon (she had ingested cloth according to the owner’s report). Laboratory tests, complete blood count, alanine aminotransferase, alkaline phosphatase, urea, and creatinine levels did not show any significant changes. Upon examination, the clinical signs were mucopurulent vaginal discharge, 5% dehydration, rectal temperature 39.1°C, mild abdominal pain on palpation, normophagy, normodipsia, and normal defecation and urinatination. Laboratory tests a new US were requested on which the uterus was observed with the presence of luminal anechoic content and increased uterine diameter (uterine horns 3.97 cm), an acoustic intestinal shadow supposedly from a foreign body,and on the leukogram, leukocytosis (23,600/mm3) due to neutrophilia with a right shift (20,532/mm3) was observed. Therapeutic ovariohysterectomy and exploratory celiotomy were chosen as therapeutic options. Celiotomy with caudoumbilical mid ventral access was performed. When the left uterine horn was identified, an attempt was made to pull it in order to expose the left ovary, but this maneuver was not successful. For this reason, the abdominal incision was enlarged cranially. At that point, a huge mass was observed in the ovary (which was supposedly the acoustic shadow of the foreign body in the descending colon/left ovary). The intestines appeared normal. Macroscopically, the mass had an irregular surface, round shape, firm consistency, and was 15 cm long x 10 cm wide. Once removed, the mass was incised in the transversal direction, purulent content, hair, and mineralized areas inside it were observed. Histopathological examination showed neoplastic proliferation, consisting of cells with elongated epithelioid shape that were arranged in long irregular bundles among well-differentiated adipose tissue. An exuberant eosinophilic matrix with extensive cystic areas filled with lamellar keratin and hairy stems covered by squamous epithelium was also observed. Extensive areas exhibiting nervous tissue. The morphological picture was compatible with teratoma. Discussion: The present report describes the concomitant presence of ovarian teratoma and pyometra in a dog. The diagnosis of pyometra requires complementary tests (laboratory and imaging). The intestinal acoustic shadow observed on the two US images obtained by two different professionals was suggestive of intestinal foreign body but was also a wrong diagnosis, which was confirmed after an exploratory celiotomy when the mass in the left ovary was identified. On the histopathological examination of this presente case, epithelial, nervous, and cartilaginous tissues were observed. This differentiation of tissues corroborated the teratoma diagnosis. Thus, the importance of an accurate diagnosis contributes to the resolution of a surgical conditions that may have had a poor prognosis when the procedure took a longer time to perform. Keywords: ovarian neoplasia, ultrasonography, OSH, pyometra. Descritores: neoplasia ovariana, ultrassonografia, OSH, piometra. Título: Ocorrência simultânea de teratoma ovariano e hiperplasia endometrial cística com piometra em cadela Labrador Retriever